An observability problem for a class of uncertain-parameter linear dynamic systems - Oprzędkiewicz, Krzysztof (Zielona Góra: Uniwersytet Zielonogórski)
An observability problem for a class of linear, uncertain-parameter, time-invariant dynamic SISO systems is discussed. The class of systems under consideration is described by a finite dimensional state-space equation with an interval diagonal state matrix, known control and output matrices and a two-dimensional uncertain parameter space.
Keywords: linear uncertain-parameter dynamic systems; observability